External Parasites on Beef Cattle - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS, 2011)
External parasites such as lice, flies, ticks, cattle grubs, and mites are a serious problem to livestock breeders. These pests are most prevalent during spring and summer months; however, Florida's warm climate permits many pests to live year-round. This revised 13-page fact sheet was written by P. E. Kaufman, P. G. Koehler, and J. F. Butler, and published by the UF Department of Entomology and Nematology, April 2011.